2021
DOI: 10.21002/seam.v15i1.13411
|View full text |Cite
|
Sign up to set email alerts
|

Entering the Global Market: The Role of Work Autonomy and Individual Global Mindset as Antecedents of Innovative Work Behavior in Defining Employee Task Performance

Abstract: "Research Aims: This study aims to highlights the role of innovative work behavior (IWB) in determining task performance. The main antecedents of IWB, namely work autonomy and individual global mindset, are discussed, as well as how these two key factors will detemine the degree of individual innovative behavior. Design/Methodology/Approach: This study uses a cross-sectional design with convenience sampling methods to collect primary data and Structural Equation Modelling (SEM) to test the hypothetical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…According to [12], there are four dimensions of innovative work behavior: idea exploration, idea creation, idea promotion, and idea Numerous studies have demonstrated the importance of innovative work behavior in the workplace [13]. Innovative work behavior is a social and independent mechanism that can enhance workplace performance [14]; frequently necessitates out-of-the-box and novel thinking, which can increase work autonomy and individual perspective [15];…”
Section: Innovative Work Behaviormentioning
confidence: 99%
“…According to [12], there are four dimensions of innovative work behavior: idea exploration, idea creation, idea promotion, and idea Numerous studies have demonstrated the importance of innovative work behavior in the workplace [13]. Innovative work behavior is a social and independent mechanism that can enhance workplace performance [14]; frequently necessitates out-of-the-box and novel thinking, which can increase work autonomy and individual perspective [15];…”
Section: Innovative Work Behaviormentioning
confidence: 99%
“…Innovative work behavior comes from the word 'innovation,' renewable with uniqueness and attractiveness (Mustika et al, 2020). One of the resources in the 21st century related to uniqueness and knowledge is the definition of innovation (Pusparini & Aryasa, 2021). In addition, innovativeness is the desire to provide experimentation and creativity for creating services, goods, excellence, technological innovations, and research findings to develop new processes (Lumpkin & Dess, 2001).…”
Section: H2: Self-leadership Has a Positive And Significant Impact On...mentioning
confidence: 99%
“…Kepemimpinan transformasional lebih meningkatkan motivasi dan kinerja para pengikutnya(Prabawati & Mutamimah, 2017). Dan alangkah lebih baik lagi jika lebih memperhatikan lagi faktorfaktor lain selain gaya kepemimpinan transformasional yang dapat mempengaruhi kinerja karyawan dimana apabila semua faktor lebih diperhatikan lebih baik lagi agar dapat menumbuhkan kinerja lebih baik agar dapat melaksanakan pekerjaan optimal(Ariyani & Hidayati, (2018), danPusparini & Aryasa, (2021). PenelitianLasiny et al, (2021), Andreani & Petrik, (2016, danEtikariena & Kalimashada, (2021) menyatakan bahwa kepemimpinan transformasional berpengaruh signifikan terhadap kinerja karyawan.…”
unclassified